A Critical Reading Process on Foreign Language Pedagogical Knowledge: Toward a Developmental Theory of Beginning Teacher Practices (The Abstract Text of A Research Paper in The Modern Language Journal) - Feni Munifatullah (Universitas Lampung, 2017)
This article discusses the abstract of the paper entitled Foreign Language Pedagogical Knowledge: Toward a Developmental Theory of Beginning Teacher Practices in The Modern Language Journal 91(07):63-82 from critical thinking standards and critical literacy supported by systemic functional grammar aspects. The analyses indicate that the text can be considered as an appropriate text considering the author, its audience, its well-established and complete structure, and a very concise purpose. The text is clear, accurate, relevant, broad, and sufficient. It is consistent to what it discusses along the text, provides the facts instead of opinions, and contains so many topics but lacks cohesive devices. Besides, the critical literacy aspects guide the reader to explore deeper into the text by using systemic functional grammar some aspect of cohesion is solved by theme progression and the use of tenses and modals. The discussion has assisted the reader to come to a conclusion that the abstract is well presented/produced.Keywords: critical thinking standards, critical thinking literacies, functional analysis DOI: http://dx.doi.org/10.23960/aksara/v18i2.pp154-168